Regulatory T Cells in Allogeneic Stem Cell Transplantation. (8th May 2013) - Michael, Maria; Shimoni, Avichai; Nagler, Arnon
Abstract : Growing evidence suggests that cellular adoptive immunotherapy is becoming an attractive though challenging approach in regulating tumor immunity and alloresponses in clinical transplantation. Naturally arising CD4+CD25+Foxp3+ regulatory T cells (Treg) have emerged as a key component in this regard. Over the last decade, a large body of evidence from preclinical models has demonstrated their crucial role in auto- and tumor immunity and has opened the door to their "first-in-man" clinical application. Initial studies in clinical allogeneic stem cell transplantation are very encouraging and may pave the way for other applications. Further improvements in Treg ex vivo or in vivo expansion technologies will simplify their global clinical application. In this review, we discuss the current knowledge of Treg biology and their potential for cell-based immunotherapy in allogeneic stem cell transplantation.